2019
DOI: 10.3389/fspor.2019.00065
|View full text |Cite
|
Sign up to set email alerts
|

People With Low Back Pain Display a Different Distribution of Erector Spinae Activity During a Singular Mono-Planar Lifting Task

Abstract: This study aimed to investigate the variation in muscle activity and movement in the lumbar and lumbothoracic region during a singular mono-planar lifting task, and how this is altered in individuals experiencing low back pain (LBP). Muscle activity from the lumbar and lumbothoracic erector spinae of 14 control and 11 LBP participants was recorded using four 13 × 5 high-density surface electromyography (HDEMG) grids. Root mean squared HDEMG signals were used to create spatial maps of the distribution of muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Regional variations in HDsEMG-torque coherence. Moreover, given that regional differences in myoelectric activity of lumbar ES is a common finding in people with CLBP [23][24][25][26][27]61 and that altered distribution of input to the motoneurons can change motor unit recruitment patterns during pain 62 , we investigated whether regional differences in sEMG-torque coherence also existed between people with CLBP and asymptomatic controls. Differences in topographical representation of coherence were observed at 50%MVC, since the lumbar ES coherence centroid in the CLBP group was displaced more cranially (suggesting higher coherence in the upper region of the muscle), while in the asymptomatic controls, the centroid of coherence was displaced towards more middle-caudal regions of the lumbar ES.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regional variations in HDsEMG-torque coherence. Moreover, given that regional differences in myoelectric activity of lumbar ES is a common finding in people with CLBP [23][24][25][26][27]61 and that altered distribution of input to the motoneurons can change motor unit recruitment patterns during pain 62 , we investigated whether regional differences in sEMG-torque coherence also existed between people with CLBP and asymptomatic controls. Differences in topographical representation of coherence were observed at 50%MVC, since the lumbar ES coherence centroid in the CLBP group was displaced more cranially (suggesting higher coherence in the upper region of the muscle), while in the asymptomatic controls, the centroid of coherence was displaced towards more middle-caudal regions of the lumbar ES.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the HDsEMG grid was placed unilaterally over the lumbar ES, 2 cm lateral to the L5 spinous process (AS controls: right side, CLBP group: most painful side) (Fig. 1 ) 23 , 24 , 26 , 36 . The electrode was placed on the most painful side for the CLBP group as it was expected that this side would show greater changes in myoelectric activity 25 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This redistribution of activity is thought to have the physiological significance of redistributing load, minimising muscle fatigue and prolonging endurance, possibly by preventing overload on the muscle fibres active at the beginning of the task. This variation in activation within regions of the same muscle appears to be of particular relevance for muscles commonly exposed to repetitive or sustained activation, such as the upper trapezius muscle (Falla et al, 2017Farina et al, 2008;Gallina et al, 2013) and the lumbar erector spinae (Abboud et al, 2015;Falla et al, 2014;Martinez-Valdes et al, 2019;Sanderson et al, 2019bSanderson et al, , 2019aTucker et al, 2009). For instance, Abboud and colleagues (Abboud et al, 2016) observed that the variability in the spatial location of the activation of the lumbar erector spinae is reduced in response to sudden trunk mechanical perturbations during the presence of fatigue.…”
Section: Spatial Redistribution Of Muscle Activity In Asymptomatic Peoplementioning
confidence: 99%